Chief complaint, treatment need and factors Affect Late Attendance to Dental Clinic in a Sample Collected from Iraqi Patients (Mustansiria Dental Journal, 2018)
This study conducted on (470) subjects attending dental clinic in Baghdad. Information was collected from all patients regarding their age, sex and chief compliant at the time of presentation. This was followed by clinical examination. Chief complaint of the majority of patients was toothache (47.02%) while the rest were come for various reasons. All of the patients examined were in need of some type of treatment. (56.60%) of patients needed conservative treatment, (14.89%) extraction, (5.79%) prosthodontic treatment, (8.64%) periodontal treatment, (2.34%) fixation of bridge, (0.2%) surgical operation and only medication were (5.74%).The factors that affect the delay attendance of dental patients to the clinic were studied after direct question to the patients who gave nearly the same causes mentionened in other previous similar studies which reflect the great need to dental health education and improvement of the dentist-patient interaction